Strengthening The Profile of Pancasila Students in Philosophical Ki Hajar Dewantara - Setiyadi, Muhammad Wahyu; Atmadja, Anantawikrama Tungga; Suastra, I Wayan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
The purpose of this study is to determine the definition of strengthening the profile of pancasisla students in the perspective of the philosophy of Ki Hajar Dewantara. This type of research is quantitative research with the method used is literature review. The educational values of Ki Hajar Dewantara are contained in the profile of pancasila students in the independent curriculum. The concept of Ki Hajar Dewantara Education is liberating education. The meaning of freedom is that everyone has the right to choose anything according to their needs and abilities without coercion, and must respect each other's independence so that it is in accordance with the educational philosophy that was triggered. Pancasila Student Profile is a form of implementation of national education goals which refers to educational policies as guidelines for educators in shaping the character of Indonesian students who continue to be maintained throughout their lives who are equipped with competence, character and behave in accordance with the values of Pancasila in the independent curriculum. There are 6 profiles of Pancasila students, namely faith, global diversity, cooperation, independence, critical and creative thinking.